Building an effective learning environment in a course in English phonetics - Łodzikowski, Kacper; Aperliński, Grzegorz (My University, 2014)
This paper presents modern online teaching methods we applied in a blended learning course in English phonetics for 1BA English philology students. Our aim is to offer suggestions on how to create a flipped-classroom-style effective learning environment that boosts learners’ autonomy and engagement with the course. The suggestions range from reusing freely available solutions such as Google Apps to showing examples of custom-developed Moodle plug-ins and web apps. The traditional approach to education has long had the teacher is in the centre, acting as the distributor of knowledge and controller of student activity. But today, students can be offered a personalised process of learning, with the teacher’s role effectively reduced to a guide who only pushes learners in the right direction. Our goal was to prepare a diversified learning environment that would inspire creativity and critical thinking in students, as well as require interaction between the learner and the material. As a theoretical framework for designing the course, we followed Nicholls (2002), Carmean and Haefner (2002) and Fullan (2012). In our paper, we discuss the following aspects of an effective learning environment and present the following methods we used to attain the desired results: 1. Social learning and how it can be fostered with the help of Google Apps to personalise students’ learning materials (Blau and Caspi 2009: 53, Pacansky-Brock 2012: 48, 117). 2. Active learning using webquests and the Moodle glossary activity type where students are required to seek information on the web, and create and share their own definitions to teach their colleagues. 3. Contextual learning that expects students to apply their knowledge in believable scenarios, e.g. a short answer activity type with an on-screen clickable keyboard containing IPA symbols for both RP and GenAm English. We highlight the usefulness of pre-programmed feedback specific for most common wrong answers. 4. Student-owned and engaging learning: following the success of such massive open online courses as Khan Academy, we supplemented pre-class readings with screencasts to cater for different learning styles. We then introduced post-class free practice activities, our flagship practice activity being an in-house developed phonetic transcriptor of RP English, which allows students to practise allophonic transcription without teacher supervision.
Paper presented at the Accents 2013 conference
Keywords: Computer-assisted language learning; e-learning; Moodle; Google Docs; phonetic transcription; phonetics teaching and learning; EFL pronunciation teaching and learning